Development of ricehusk ash reinforced bismaleimide toughened epoxy nanocomposites - Kanimozhi, K.; Sethuraman, K.; Selvaraj, V.; Alagar, M. (Frontiers in Chemistry, 2014)
Recent past decades have witnessed remarkable advances in composites with potential applications in biomedical devices, aerospace, textiles, civil engineering, energy, electronic engineering, and household products. Thermoset polymer composites have further enhanced and broadened the area of applications of composites. In the present work epoxy-BMI toughened-silica hybrid (RHA/DGEBA-BMI) was prepared using bismaleimide as toughener, bisphenol-A as matrix and a silica precursor derived from rice husk ash as reinforcement with glycidoxypropyltrimethoxysilane as coupling agent. Differential scanning calorimetry, electron microscopy, thermogravimetric analysis, and goniometry were used to characterize RHA/DGEBA-BMI composites developed in the present work. Tensile, impact and flexural strength, tensile and flexural modulus, hardness, dielectric properties were also studied and discussed. The hybrid nanocomposites possess the higher values of the glass transition temperature (Tg) and mechanical properties than those of neat epoxy matrix.